THU0556 ARTERIAL AND VENOUS THROMBOTIC EVENTS IN IGG4-RELATED DISEASE: A NATIONAL OBSERVATIONAL RETROSPECTIVE STUDY. (June 2019) - Gutierrez, Blandine; Grados, Aurélie; Palat, Sylvain; Ribeiro, Emmanuel; Gouellec, Noémie Le; Haroche, Julien; Papo, Thomas; Harlé, Jean-Robert; Ly, Kim; Schleinitz, Nicolas; Ebbo, Mikael; ,
Abstract : Background: IgG4-related disease (IgG4-RD) is a fibro-inflammatory disorder that can affect virtually every organ. Although arterial involvements have been reported, no studies have examined the occurrence of arterial or venous thrombotic events in these patients. Objectives: To explore the frequency, the characteristics, and risk factors of arterial and venous thrombotic events in IgG4-related disease patients. Methods: An observational, descriptive, retrospective study was conducted from a multicentric national case registry for IgG4-RD. Patients fulfilled the Comprehensive Diagnostic Criteria (CDC) for IgG4-RD, and all patients with arterial or venous thrombotic events confirmed by imaging during follow-up were analyzed. Clinical, radiological, biological, histological and therapeutic characteristics were retrospectively collected using a standardized online data sheet. Results obtained in patients with thrombosis were compared to those without thrombosis. Results: One hundred eighty-nine patients with IgG4-RD (135 men/54 women, median age 61 years) were included. During a 12-months median follow-up, one or more arterial thrombotic events occurred in 10 patients and venous thrombotic events in 16 (5.3 and 8.5 events/100 patient-years, respectively). Arterial complications (coronary artery disease n=5, lower limb peripheral arterial disease n=2, mesenteric ischemia, transient ischemic attack, and carotid thrombosis: n=1) occurred on average 30 months [0-140] after the first symptoms of IgG4-RD. They were inaugural in 2 patients without any cardiovascular risk factor, and associated with IgG4-RD arterial involvement in 3 (coronary aneurysms n=2, leg arteritis n=1). Among patients with arterial thrombosis, 60% had systemic involvement (≥3 organs involved), 89% elevated serum IgG4 (> 3N in 56%), and 57% CRP >10 mg/l. Only 5/10 were treated with steroids at the time of arterial complication, and 4 had never been exposed to steroid therapy. Renal involvement was associated with the occurrence of an arterial thrombotic event ( p = 0.03 ). Venous thromboembolic complications (deep venous thrombosis (DVT) n=12, pulmonary embolism n=4) occurred on average 24 months [0-164] after the first symptoms of IgG4-RD, but were inaugural in 6 patients. Usual venous thrombosis risk factors were found in only 3/16. Seven patients had retroperitoneal fibrosis (RPF), 2 had mediastinal fibrosis, 60% had localized IgG4-RD (≤2 organs involved), serum IgG4 level was normal in 67% and CRP <10 mg/l in 79%. Nine patients were on steroids at the time of venous thrombosis. RPF was more frequent in the group of IgG4-RD patients with a venous thrombotic event ( p = 0.05 ), and largely associated with DVT in a multivariate analysis (OR=8.36 [2.25-35.93], p = 0.002 ). Conclusion: Arterial and venous thrombotic complications are common in IgG4-RD patients. While arterial events are associated with mulitorgan involvement and elevated serum IgG4, venous thrombotic complications appear to affect more likely patients with compressive localized forms of the disease, such as RPF. Mechanisms responsible for this over-risk and clinical benefit of a preventive platelet antiaggregant or anticoagulant treatment in high risk of thrombosis subgroups remain to be evaluated. Disclosure of Interests: None declared